A case report of acute promyelocytic leukemia with myeloid sarcoma of the lumbar spine and literature review - Yiwen Du; Kun Yang; Yantao Ling; Ying Zhang; Yuping Gong (Frontiers in Medicine)
Acute promyelocytic leukemia (APL) presenting solely as myeloid sarcoma (MS) is extremely rare. This report describes a 53-year-old male who presented with low back pain and a movement disorder in his lower limbs. MRI and PET/CT scans of the lumbar spine revealed an intraspinal mass. Pathological analysis of the surgically resected mass identified it as myeloid in origin. Routine blood tests were unremarkable, and bone marrow smears and immunophenotyping showed no evidence of abnormal myeloblasts or promyelocytes. However, bone marrow aspirates testing for acute leukemia fusion genes by qPCR revealed the presence of the PML::RARA fusion. Further investigation via FISH confirmed the fusion in both the bone marrow and the extramedullary mass. The patient was ultimately diagnosed with isolated promyelocytic extramedullary sarcoma (MS/APL). Treatment with all-trans retinoic acid and arsenic trioxide alleviated the back pain and restored the patient’s mobility. After 1 year of consolidation therapy, bone marrow smears confirmed sustained remission, and the PML::RARA fusion gene was undetectable. In addition to this case, we review 41 other APL patients with extramedullary sarcoma as their first symptom (MS/APL) at the time of diagnosis and provide an analysis of these cases.